2021
DOI: 10.3390/v13030518
|View full text |Cite
|
Sign up to set email alerts
|

Selective Interaction of Sugarcane eIF4E with VPgs from Sugarcane Mosaic Pathogens

Abstract: Eukaryotic translation initiation factor 4E (eIF4E) plays a key role in the infection of potyviruses in susceptible plants by interacting with viral genome-linked protein (VPg). Sugarcane (Saccharum spp.) production is threatened by mosaic disease caused by Sugarcane mosaic virus (SCMV), Sorghum mosaic virus (SrMV), and Sugarcane streak mosaic virus (SCSMV). In this study, two eIF4Es and their isoform eIF(iso)4E and 4E-binding protein coding genes were cloned from sugarcane cultivar ROC22 and designated SceIF4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…These results indicate a link between EXA1 and viral translation depending on eIF4Es. Several studies in various plants have suggested that the interactions between eIF4Es and VPgs are responsible for eIF4E -mediated resistance [ 76 79 ]. However, the interaction between eIF4Es and VPg/NIa alone cannot fully elucidate the role of eIF4Es in the infection cycle of potyviruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate a link between EXA1 and viral translation depending on eIF4Es. Several studies in various plants have suggested that the interactions between eIF4Es and VPgs are responsible for eIF4E -mediated resistance [ 76 79 ]. However, the interaction between eIF4Es and VPg/NIa alone cannot fully elucidate the role of eIF4Es in the infection cycle of potyviruses.…”
Section: Discussionmentioning
confidence: 99%
“…S8b ). In a recent study of sugarcane, the interactions between ScnCBP and VPgs of several sugarcane mosaic pathogens were detected only in bimolecular fluorescence complementation (BiFC), but not in Y2H assay [ 79 ]. Thus, we cannot exclude the possibility that the VPg or some other proteins of PVY may also be involved in the resistance mediated by StEXA1 and StnCBP.…”
Section: Discussionmentioning
confidence: 99%
“…Recessive resistance genes have become a very important resource in plant breeding for virus resistance ( Truniger and Aranda, 2009 ). eIF4Es are the most extensively studied recessive resistance genes involved in the infection of various viruses ( Hashimoto et al, 2016 ; Xu et al, 2017 ; Yang et al, 2021 ). This study for the first time reports that StnCBP , a member of the eIF4E family in potato, is involved in PVS infection as a recessive resistance gene.…”
Section: Discussionmentioning
confidence: 99%
“…They are also the most extensively studied susceptibility genes ( Lellis et al, 2002 ), and particular research attention has been paid to the relationship between eIF4E/eIF(iso)4E and potyvirus infection. For instance, mutation in eIF4E/eIF(iso)4E resulted in loss of susceptibility to potyviruses in multiple hosts, such as Arabidopsis, tomato, pepper, lettuce, pea, peanut, and sugarcane ( Ruffel et al, 2002 , 2005 ; Nicaise et al, 2003 ; Gao et al, 2004 ; Xu et al, 2017 ; Yang et al, 2021 ). In most cases, the interaction between eIF4E/eIF(iso)4E and the viral genome-linked proteins (VPgs) of potyviruses is required for virus infection ( Léonard et al, 2000 ; Charron et al, 2008 ; Tavert-Roudet et al, 2017 ; Yang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation